Career decision making among Malaysian University students - Md Rami, Ahmad Aizuddin; Mohd Zaini, Siti Nadhirah; Abd Aziz, Mohd Faiq (Human Resource Management Academic Research Society, 2021)
Career decision making is a huge challenge for undergraduate students. Indeed, the challenges they encounter when making a career choice during the transition periods are common problems for university students. Hence, this quantitative study used a correlational research design to investigate the relationship between academic achievement and self-concept with career decision making among final year students in Universiti Putra Malaysia. A total of 171 final year students participated in the study. The academic achievement of the students was measured using the current CGPA. The Academic Self-Concept Scale (ASC) developed by Liu and Wang (2005) and Career Decision Scale (CDS) (Osipow et al., 1976) were administered to the sample to assess their self-concept and career decision, respectively. The study results show that there is no significant relationship between academic achievement and career decision making. Simultaneously, there is a significant relationship between academic self-concept toward career choice among undergraduate students. These findings add to our knowledge in helping students to make better decisions about their future careers by enhancing their academic self-concept.